Risk Factors for Narcotics, Psychotropics, and Addictive Substances (NAPZA) Use in Adolescents: A Systematic Review - Sekila Yuniarizka; Syarifuddin Wahid; Muhammad Alim Jaya; St. Wahida Jalil; R. Joko Maharto (Journal of Asian-african Focus in Health, 2026)
The use of Narcotics, Psychotropic Substances, and Addictive Substances (NAPZA) among adolescents is a global public health issue that continues to increase. Adolescents are a vulnerable group to risky behaviors due to biological, psychological, and social changes. This study aims to identify and analyze the risk factors of NAPZA use among adolescents using a systematic review approach. The research method applied the PICO framework with literature searches conducted in PubMed and Google Scholar databases within the 2021-2025 period. A total of 148 articles were initially identified, and after the selection process, 18 articles were included as the main sources of analysis. In addition, 5 national journal articles were included as supporting references, resulting in a total of 23 analyzed articles. The data were extracted, classified, and analyzed using a scoring approach based on three categories of risk factors: individual, family, and social-environmental factors. The results indicate that the risk factors for NAPZA use among adolescents are multifactorial. Based on frequency analysis, social and environmental factors were the most dominant, appearing in 21 articles, followed by individual factors in 20 articles and family factors in 18 articles. Individual factors include depression, anxiety, low self-control, and curiosity; family factors include lack of parental supervision, family conflict, and economic conditions; while social and environmental factors include peer influence, ease of access to substances, and living environment conditions. Peer influence was identified as the most dominant and consistently reported risk factor across countries. Additionally, variations in risk factors across countries were influenced by social, cultural, and economic conditions. Therefore, NAPZA use among adolescents is a complex phenomenon that requires comprehensive and context-specific prevention approaches.